2022
DOI: 10.1227/neu.0000000000002044
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Pressure Monitoring in Patients With Severe Traumatic Brain Injury: Extension of the Recommendations and the Effect on Outcome by Propensity Score Matching

Abstract: BACKGROUND: Intracranial pressure (ICP) monitoring is recommended for patients with traumatic brain injury (TBI) with a Glasgow Coma Scale (GCS) <9 on admission and revealing space-occupying lesions or swelling on computed tomography. However, previous studies that have evaluated its effect on outcome have shown conflicting results. OBJECTIVE: To study the effect of ICP monitoring on outcome after adjustment of patient's characteristics imbalance and determine the potential benefit on patients with higher GCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The clinical relevance of ICP monitoring has been demonstrated in a myriad of studies and treatment parameters guided by ICP have been associated with improved outcome(s) and mortality. [3,10,11] A threshold of 22 mmHg has been de ned as pathological by the Brain Trauma Foundation guidelines; such ICPs warrant an escalation of medical and/or surgical care. [1] Therefore, a simple and reliable measure of ICP is crucial as physicians/surgeons manage critical ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical relevance of ICP monitoring has been demonstrated in a myriad of studies and treatment parameters guided by ICP have been associated with improved outcome(s) and mortality. [3,10,11] A threshold of 22 mmHg has been de ned as pathological by the Brain Trauma Foundation guidelines; such ICPs warrant an escalation of medical and/or surgical care. [1] Therefore, a simple and reliable measure of ICP is crucial as physicians/surgeons manage critical ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial pressure (ICP) monitoring is critical in the clinical management of patients with intracranial insults/lesions. [1][2][3] Monitoring with intracerebral pressure probes has become more prevalent as compared to ventricular drain measurements (i.e., the "gold standard"). [4][5][6] It is however prudent to note that no consensus exists with regard to which ICP monitoring modality is ultimately employed clinically.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of ICP monitoring has been demonstrated in a myriad of studies and treatment parameters guided by ICP have been associated with improved outcome(s) and mortality. [3,10,11] A threshold of 22 mmHg has been defined as pathological by the Brain Trauma Foundation guidelines; such ICPs warrant an escalation of medical and/or surgical care. [1] Therefore, a simple and reliable measure of ICP is crucial as physicians/surgeons manage critical ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial pressure (ICP) monitoring is critical in the clinical management of patients with intracranial insults/lesions. [1][2][3] Monitoring with intracerebral pressure probes has become more prevalent as compared to ventricular drain measurements (i.e., the "gold standard"). [4][5][6] It is however prudent to note that no consensus exists with regard to which ICP monitoring modality is ultimately employed clinically.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients in the non-ICP monitoring arm received massive anti-intracranial hypertension therapies. Other studies, which were done retrospectively, showed an improved outcome and lower mortality in ICP-steered treatment [7][8][9]. Recently, the results of the Synapse-ICU observational trial confirmed that patients in whom ICP was monitored not only had higher therapeutic intensity levels to lower ICP but also better neurological outcome at 6 months (extended Glasgow Outcome Scale, GOSE).…”
Section: Intracranial Pressurementioning
confidence: 97%